Medical Criminal Law and Malpractice (Aspects Criminal Liability of Internal Doctors Health services) - Beni Satria (International Journal of Society and Law, 2024)
Public health is the main focus in the development of the health service system. Doctors as the main pillar in providing these services have significant legal responsibilities. This research discusses aspects of medical law and malpractice related to the criminal liability of doctors in the context of health services. Within the framework of health law, the basic principles governing medical practice and their relationship with the rights and obligations of doctors are analyzed. In addition, an in-depth review was carried out on the definition and elements of malpractice, as well as the role of criminal law in regulating violating actions that may be carried out by doctors in carrying out their practice. Through literature study and case analysis, this research identifies factors that may lead to criminal liability of doctors, including misdiagnosis, non-standard treatment, and violations of professional ethics. Apart from that, challenges and changes in the medical criminal law system are also discussed that can influence the assessment of malpractice. The results of this research contribute to further understanding of the dynamics of doctors' criminal liability in health services, while highlighting the need to increase regulatory clarity to protect patient rights and provide justice to doctors. The practical implications of these findings can help policy makers and legal practitioners in developing more effective guidelines in handling malpractice cases in the health sector.